The Effects of Particle Mesh and Temperature on Pyrolysis Spirulina platensis Residue (SPR): Pyrolysis Yield and Bio-Oil Properties - Siti Jamilatun; Arief Budiman; Ilham Mufandi; Agus Aktawan; Nabila Fauzi; Defiani Putri Denanti (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
Microalgae is the third generation of biomass as renewable energy, a future energy source for making bio-oil. The purpose of this research is to examine the biomass from microalgae Spirulina platensis residue (SPR) using the pyrolysis process, to investigate the effect of particle mesh and temperature on the pyrolysis process, to determine the bio-oil properties, including density, pH, color, flame power, and conversion. Fixed bed reactor used for SPR pyrolysis with dimensions of 4.4 cm outside diameter, 4.0 cm inside diameter, and 60.0 cm reactor height. The temperature controls have been fitted from 300-600 °C combined with a 14-16 °C/minute heating rate. Spirulina platensis residue of 50 grams with various particle mesh (80 and 140 mesh) was fed to the reactor. From the experiment results, the particle mesh and temperature process are influenced by bio-oil yield, water phase, gas yield, biochar yield, conversion, and bio-oil properties, including density, pH, flame power, and color. One hundred forty mesh particles at a temperature of 500 °C showed the highest bio-oil yield with a yield of 22.92%, then the water, charcoal, and gas phases were 27.98, 18.84, and 30.26%, with a conversion of 81.16%. At the same time, 80 mesh particles at 500 °C yielded bio-oil, water, charcoal, and gas phases of 19.66, respectively; 23.10, 27.90, and 29.34%, with a conversion of 72.10%. In addition, density, pH, color, and flame power are described in this study.